Dampak Boikot Starbucks terhadap Rantai Pasok Global ke Lokal serta Pengembangan UMKM Kopi - Cayla Salsa Azhar; Farah Syaima Raihanada; Rianthi Agnesia Nareshwari; Rinandita Wikansari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This research explores the response to the global supply chain and the growth of local coffee Micro, Small and Medium Enterprises (MSMEs) in Indonesia as a result of the boycott movement against the international brand, Starbucks. By using quantitative methods and a case study approach, as well as analyzing financial reports and sales data, this research reveals interesting market dynamics. The research results show that the boycott campaign driven by social issues has succeeded in shifting consumer preferences in Indonesia. There has been a significant increase in local coffee consumption, especially Kopi Kenangan, which has succeeded in capitalizing on this momentum. On the other hand, Starbucks experienced a drastic decline in global revenue and lost considerable market value. Further analysis based on supply chain theory and consumer behavior reveals that Indonesian consumers are increasingly aware of the impact of their consumption on local social and economic issues. This encourages them to choose local products as a form of support for MSMEs and the domestic economy. These findings highlight the important role of consumer movements in shaping the market landscape. For policy makers, this research provides recommendations for creating a business environment that is conducive to the growth of MSMEs, including support in terms of financing, training and market access. Meanwhile, for business people, this research emphasizes the importance of building brands that are relevant to consumer values and responsive to social issues. This research highlights the importance of supporting local products amidst global market dynamics.